Relationship between religiosity/spirituality and work overload of the informal caregiver (Research, Society and Development, 2023)
Evaluate the correlation between religiosity/spirituality and the work overload of informal caregivers. Cross-sectional, quantitative study carried out in Vitória, ES, Brazil. From December 2018 to April 2019, 83 informal bedridden/in-home caregivers participated, To collect data, three research instruments were used to analyze sociodemographic characteristics, informal caregiver work overload and Brief Multidimensional Measure of Religiosity/Spirituality (BMMRS-p). There was an average age of 51 to 60 years old, mostly women. The overload is moderate to severe in 47.0% of the cases, the presence of God was identified within the BMMRS-p in 51% and there was no correlation between spirituality and work overload. Caregivers have a higher prevalence of overload in the act of caring, as the degree of close kinship with the patient, however, the act of caring did not have a directly proven correlation with spirituality/religiosity.